MATHEMATICAL MODEL OF THE POWER SUPPLY SYSTEM CONTROL - USENIK, Janez (Journal of Energy Technology, 2024)
In this article, a simple mathematical model of a continuous stochastic power supply system is described. Some analytical approaches have been developed to describe the influence of production and stock, i.e. additional capacities on a hierarchical spatial pattern and demand. Using the Laplace transform, it is possible to solve the system of differential equations, which are represented with the continuous model. Due to the stochastic nature of system inputs, the optimality criteria with the Wiener filter are satisfied. The inverse Laplace transform is calculated with residues in the complex space. Furthermore, an interesting and efficient approach with fuzzy logic is used, which is presented at the end of this article.